Membangun Etos dan Kearifan Lokal melalui Foklor: Studi Kasus Foklor di Tembalang Semarang - Elsa Fitrianita; Fanny Widyasari; Widiastri Indah Pratiwi (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
This study aims to determine the relationship between folklore and work ethos in Tembalang District. In the cultural inheritance of society internalize through oral culture or commonly referred to as folklore. The method of research is done by primary data collection (interview) and secondary (literature study). Primary data collection through taking five sample villages in Tembalang District. The informants we obtained in folklore research came from core informants and ordinary informants totaling 8 people. The analysis used qualitative techniques by describing the data obtained. The results showed that the Tembalang District community had folklore divided into three types, namely oral literature (oral folklore), performance folk arts (performing arts), and folk custom social (people's social habits). Folklore that develops into a local tradition with an understanding of local wisdom will preach beliefs in a spirit of togetherness and can make a community identity so that it is also realized in the identity of individuals who can create ethos in society.